A membrane technology of separating the basic aviation kerosene from petroleum - Burtna, Inessa; Gachechiladze, Otar (Eastern-European Journal of Enterprise Technologies, 2016)
The study focuses on the problems associated with separating kerosene from petroleum and subsequent applying it as a main component of aviation kerosene. Traditional technologies of separating the basic kerosene from crude oil solve the problem of producing AK only partially. Convection technologies cannot guarantee obtaining the basic kerosene with the same physical and chemical parameters that are strictly limited in modern jet fuel. The article presents some basic parameters of aviation kerosene and the same parameters of kerosene produced by distillation. Comparison of these parameters shows that the required quality of aviation kerosene requires significant transformations of the basic kerosene and involves tangible costs. The situation drastically changes with the use of membrane technologies of crude oil refining, namely, the pervaporation technology of kerosene separation. The efficiency of this technology is proved by comparison of properties of the basic kerosene produced by means of different technologies. The use of special polymeric membranes allows recovering “pure” kerosene fractions, not “polluted” with components of adjacent fractions, at low temperature modes and under atmospheric pressure, which permits controlling the composition and properties of the basic kerosene. In addition, polymeric membranes are acidresistant, waterproof, and significantly limit the penetration of sulfur compounds. All this allows producing the basic AK with the required parameters, which reduces the number of additional technological processes and additives, and, therefore, decreases costs of producing aviation kerosene (AK).